Patient Perspectives on Pharmacotherapy of Alcohol Dependence - Wellensiek, Julian; Specka, Michael; Just, Johannes; Banger, Markus; Bonnet, Udo; Scherbaum, Norbert (Pharmacopsychiatry, 2023)
Introduction Pharmacotherapy with drugs like naltrexone or acamprosate is a well-evaluated element in the treatment of alcohol dependence (AD). However, in many countries, these medications are rarely administered. The objective of the present study was to identify from patients’ perspective factors that prevent the initiation and compliance with pharmacological treatment of AD.Methods Patients from inpatient alcohol withdrawal treatment underwent a standardized interview. Questions included socio-demographic data, history of AD, treatment history, knowledge and personal experience regarding pharmacotherapy of AD, and personal views about the causes of AD.Results Three hundred patients (mean age 47.3 years, 27.7% female, mean duration of AD 8.9 years, 67% with a history of previous inpatient withdrawal treatment) were included. The majority of patients (58.7%) already knew drugs for the pharmacotherapy of AD. Thirty percent had ever used such medications, most often acamprosate. Except for disulfiram, pharmacotherapy of AD had lasted only a few weeks, on average. Medication usually had been applied without additional psychotherapy. No severe side effects were reported. Patients had often stopped pharmacotherapy on their own, when assuming they had reached stable abstinence. Openness to start pharmacotherapy for AD was currently stated by 67% of the total sample. In multiple logistic regression, openness was predicted by having a concept of AD as a medical disease and by a shorter duration of AD.Discussion To improve the administration of pharmacotherapy for AD implementation strategies should be systematically developed and evaluated with a focus on the concept of AD as a medical disease.
Keywords: alcohol dependence; pharmacotherapy; anti-craving substances; disulfiram; patient perspective